Impact of Chronic Statins Use on the Development of Esophagitis in Patients with Gastroesophageal Reflux Disease - Tawfik Khoury; Amir Mari; Hana Amara; Mohamed Jabaren; Abdulla Watad; Wiliam Nseir; Wisam Sbeit; Mahmud Mahamid (Canadian Journal of Gastroenterology and Hepatology, 2019)
Background and Aims. We aimed to assess whether chronic statins used (> 6 months) were protective of the development of esophagitis in patients with gastroesophageal reflux disease. In the presence of esophagitis, complications such as strictures, Barrett's esophagus, and adenocarcinoma were the most common. Statins, lipid lowering drugs with a pleiotropic effect, are recently implicated in various pathologies. Nevertheless, the possible impact of statins in esophagitis development has never been assessed. Methods. We performed a retrospective, cross-sectional, single center study that included 4148 gastroesophageal reflux disease patients from 2014 and 2018 at EMMS Nazareth Hospital. We divided the patients into 5 groups. The groups were split into positive control group, which was the nonesophagitis group, and the other 4 groups were A-D (as per Los Angeles classification). Results. Overall, out of the 4148 patients included, 48% were males and 2840 patients were in the control group. In groups A, B, C, and D there were 818, 402, 72, and 16 patients, respectively. Logistic regression analysis revealed that chronic statins usage is protective by preventing development esophagitis (OR 0.463 [95%CI 0.370–0.579], p < 0.0001). NSAIDS use, Hiatus hernia, and H. pylori were promoting factors (OR, 1.362, 1.779, and 1.811; 95% CI, 1.183-1.569, 1.551-2.040, and 1.428-2.298; P<0.0001, P<0.0001, and P<0.0001, respectively). Conclusion. Using chronic statins was protective to the development of esophagitis among GERD patients. Our findings of potential clinical application mandate further randomized controlled trials to better assess the impact of statins on esophagitis.